Optimalisasi Pengelolaan Dana Zakat dalam Mendukung Program Pendidikan Beasiswa Cendekia BAZNAS Kota Tangerang - Suardi, Didi; Nurul Lailah, Luthfiatun; R. Simatupang, Aisyah Defy; Azwar, Martavevi; Septi, Iti; Tidjani, Shofiah; Komariyah, Oom (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the optimization of zakat fund management in supporting the BAZNAS Tangerang City Cendekia Scholarship program. This study uses a qualitative method with a case study approach. The data used were obtained from interviews, observations, and documentation collected directly from BAZNAS Tangerang City. The results of this study indicate that the management of zakat funds through the BAZNAS Tangerang City Cendekia Scholarship education program has been running optimally. Optimization is carried out by distributing funds effectively, efficiently, on target, and long-term. The program is supported by internal and external factors. In addition, there are inhibiting factors in implementing the program but they are not very significant, so the management of funds in this program can be said to be quite optimal. The results of this study serve as a basis for BAZNAS and other zakat institutions to maintain and develop educational programs. Because the BAZNAS Tangerang City Cendekia Scholarship has succeeded in becoming an effective program in allocating zakat funds for education. This research is in line with the results of research conducted by Asep Kurniawan (2023) which explains that this scholarship program has been quite effective during its three-year run. The benchmarks for effectiveness are seen from the fluid adaptation of team solidarity, the quality of the programs implemented, the work achievements obtained, job satisfaction, and views from external parties.